2005
DOI: 10.1103/physrevb.71.212507
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flux pinning in neutron irradiatedMgB2

Abstract: We study the effect of neutron irradiation on the critical current density J c of isotopically pure polycrystalline Mg 11 B 2 samples. For fluences in the range 10 17 -10 18 cm -2 , J c is enhanced and its dependence on magnetic field is significantly improved: we demonstrate that, in this regime, pointlike pinning centers are effectively introduced in the system proportionally to the neutron fluence.Instead, for larger fluences, a strong suppression of the critical temperature accompanied by a decrease of bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 18 publications
(10 reference statements)
5
71
0
Order By: Relevance
“…Several superconducting properties of the samples have been reported in Refs. [13,14,15,16,17]. For simplicity and ease of comparison, we label the two samples as in Ref.…”
Section: Experimental Apparatus and Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several superconducting properties of the samples have been reported in Refs. [13,14,15,16,17]. For simplicity and ease of comparison, we label the two samples as in Ref.…”
Section: Experimental Apparatus and Samplesmentioning
confidence: 99%
“…In any cases, the inclusion of defects, besides to change the inter-band scattering, might increase the upper critical field and the critical current, strongly affecting the fluxon dynamics. Very recently, the effects of neutron irradiation have extensively been investigated on polycrystalline Mg 11 B 2 [13,14,15,16,17]. It has been shown that irradiation leads to an improvement in both critical field and critical current density for an exposure level in the range 1 ÷ 2 × 10 18 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large engineering applications have been hampered so far by low density and poor flux pinning behaviour of MgB 2 which induces degradation of J c in high magnetic fields. Many researchers have attempted to improve the flux pinning behaviour through several types of processes such as high energy ion-irradiation 11 , chemical doping using different metallic and non-metallic phases and nano particles admixing [12][13][14] . Recent studies have shown that chemical doping may be effective and feasible approach for increasing critical current density of MgB 2 superconductors [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…The inter-grain connectivity (A F ) of the samples varies between 11%-20%. All the additives result in a critical current density (J c ) higher than the stoichiometric MgB 2 sample, where the highest values (e.g., J c (1 T and flux pinning [10][11][12][13][14][15] has been a very active research area. Despite the effort, MgB 2 continues to pose challenges linked with inter-grain connectivity, pinning, and anisotropy.…”
mentioning
confidence: 99%